Photostability Testing of a Third-Generation Retinoid-Tazarotene in the Presence of UV Absorbers - Agata Kryczyk-Poprawa; István Zupkó; Péter Bérdi; Paweł Żmudzki; Justyna Popiół; Bożena Muszyńska; Włodzimierz Opoka (MDPI AG, 2020)
Exposure of a drug to UV irradiation could affect its physicochemical properties. Hence, photostability testing is essential for topically administered drugs. Tazarotene, a receptor-selective, third-generation retinoid, is commonly used to treat acne vulgaris and psoriasis. In the present study, an in-depth analysis of the photostability of tazarotene in ethanolic solution in the presence of zinc oxide and/or titanium dioxide as well as benzophenone-type UV filters was performed. Eleven presumed products were derived from the photocatalytic degradation of tazarotene using ultra-performance liquid chromatography-tandem mass spectrometry, and transformation pathways were proposed. The degradation process mainly affected the 4,4-dimethyl-3,4-dihydro-2H-thiopyran moiety. The fragments most susceptible to oxidation were the methyl groups and the sulfur atom. Moreover, in the presence of sulisobenzone, under UV irradiation, tazarotene was subjected to a degradation process, which resulted in two photodecomposition products. In silico studies performed by OSIRIS Property Explorer demonstrated that five of the degradation products could be harmful in terms of the reproductive effects, which are associated with 3,4-dihydro-6-methyl-2H-1-benzothiopyran 1,1-dioxide, while one of them demonstrated potential irritant activity. The cytotoxic properties of the degradation products of tazarotene were assessed by MTT assay on a panel of human adherent cancer cells. Time- and concentration-dependent growth inhibition was evidenced in ovary (A2780) and breast (MDA-MB-231) cancer cell lines. The potential implication of the outcomes of the present research requires further studies mainly concerning the photostability of tazarotene in the topical formulations.